Analisis Adab Dalam Film Cahaya Cinta Pesantren - Taufiq Hidayat Shidiq (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to find out the Islamic manners contained in the film Cahaya Cinta Pesantren and to analyze the manners contained in the film Cahaya Cinta Pesantren. This type of research is qualitative research, content analysis and the approach used is a descriptive approach. The primary data source of this research is the film Cahaya Cinta Pesantren. The results of this study show that the manners raised in the film Cahaya Cinta Pesantren were successfully conveyed very well by the director, Raymond Handaya. From the beginning to the end, he was able to describe Islamic values consistently, including the application of sharia dress manners. For more than two hours of film, there is not a single scene that shows the player uncovering the awrah, reflecting adherence to the principle of modesty in dress. In addition, this film also strictly maintains the limits of interaction between men and women, by not showing scenes of holding hands with each other.